Self-Efficacy and Performance in Mathematics of Science High School Students - Alviar-Eisma, Sarah; Campoamor-Olegario, Lizamarie (Alipato, A Journal of Basic Education; Vol 12 (2021): 25th Anniversary Issue, 2022)
It is assumed that being in a competitive science high school (SHS) affects the students' mathematics self-efficacy (MSE) or their belief that they can succeed in Mathematics. Low MSE may result in poor mathematics performance (MP) and may lead to students’ underperformance. This study aimed to identify which sources of MSE contributed to the MSE of 144 Grade 11 SHS students in the Philippines and if there was a significant relationship between MSE and MP, and if the former could predict the latter. A mixed-method approach was adopted using statistical analysis by PLS-PM and thematic analysis of semi-structured interviews with 23 students. Findings showed that mastery and vicarious experiences influenced the SHS students’ MSE but there was no significant relationship between MSE and MP. Mastery experiences (ME) and efforts in learning math skills, not just MSE, were strong predictors of MP. It is recommended that teachers become aware of the students’ efficacy threshold to experience mastery through increasing difficulty. Collaborative learning is essential to lessen negative vicarious experiences. Keywords: mathematics self-efficacy, sources of mathematics self-efficacy, mathematics performance, Science high school students